The Relationship of Self Efficacy and Family Support with Self Care in Elderly Age Diabetes Mellitus Type II - Imas Sartika; Mustikasari Mustikasari; Rohman Azzam (Jurnal Berita Ilmu Keperawatan, 2023)
Family support is an element that is very closely related to the elderly. Increased self-efficacy will control symptoms, treatment and lifestyle so that patients are able to adapt to their conditions. This study will analyze the relationship between self-efficacy and family support with self-care in the elderly with type II diabetes mellitus at the Cipondoh Public Health Center, Tangerang City. Methods: This research design is a quantitative research with a cross sectional approach. Sampling using purposive sampling with a total of 167 respondents. Collecting data using self efficacy questionnaire for diabetes scale, HDFSS and DSMQ. Results: bivariate analysis using the chi square test stated that there was a relationship between self-efficacy and self-care for type II DM patients, namely (p = 0.016) OR 2. 474 means that self-efficacy has a chance of 2,474 times good self-care. There is a relationship between family support for self-care (p = 0.004) with an OR value of 4.033 which means that family support has a good chance of 4.033 times having good self-care. Multivariate analysis showed that the variable most related to self care was family support with OR = 3.682. It is hoped that health workers at the Cipondoh Health Center in Tangerang City will improve health promotion through PTM posbindu activities, both in the form of education about self-efficacy and family support, which can be done by involving the family. Multivariate analysis showed that the variable most related to self care was family support with OR = 3.682. It is hoped that health workers at the Cipondoh Health Center in Tangerang City will improve health promotion through PTM posbindu activities, both in the form of education about self-efficacy and family support, which can be done by involving the family. Multivariate analysis showed that the variable most related to self care was family support with OR = 3.682. It is hoped that health workers at the Cipondoh Health Center in Tangerang City will improve health promotion through PTM posbindu activities, both in the form of education about self-efficacy and family support, which can be done by involving the family.